2016
DOI: 10.1016/j.freeradbiomed.2016.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of radicals following injury or acute stress in peripheral nerves with activatable fluorescent probes

Abstract: Peripheral nerve injury evokes a complex cascade of chemical reactions including generation of molecular radicals. Conversely, the reactions within nerve induced by stress are difficult to directly detect or measure to establish causality. Monitoring these reactions in vivo would enable deeper understanding of the nature of the injury and healing processes. Here, we utilized near-infrared fluorescence molecular probes delivered via intra-neural injection technique to enable live, in vivo imaging of tissue resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…There were four different hand-held systems (PDE n = 13, Visionsense n = 1, Fluobeam n = 2, and HyperEye n = 1) [ 7 19 , 44 46 , 49 ], one non-hand-held system (FLARE n = 8) [ 36 43 ], and three types of microscopes with an integrated NIRF (SPY n = 16, LEICA n = 2, and Pentero n = 1) [ 20 – 35 , 47 , 48 ] suitable for fluorescence image guidance. In one study, a prototype was used which was not further specified [ 51 ]; three articles unfortunately did not state what kind of imaging system was used [ 52 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were four different hand-held systems (PDE n = 13, Visionsense n = 1, Fluobeam n = 2, and HyperEye n = 1) [ 7 19 , 44 46 , 49 ], one non-hand-held system (FLARE n = 8) [ 36 43 ], and three types of microscopes with an integrated NIRF (SPY n = 16, LEICA n = 2, and Pentero n = 1) [ 20 – 35 , 47 , 48 ] suitable for fluorescence image guidance. In one study, a prototype was used which was not further specified [ 51 ]; three articles unfortunately did not state what kind of imaging system was used [ 52 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five different preclinical dyes were tested in animal studies in order to detect nerve injury by intraneural injection of the dye [ 53 , 54 ]. One study labeled fat cells with a specific fluorescent dye to enable the investigation of the amount of fat cells, which survived after autologous fat cell transportation [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By utilizing optical imaging techniques, earlier nerve inflammation can be detected noninvasively. [53] Last but not least, nerve density visualization in tumors will help in the assessment of cancer aggressiveness and prognosis, due to the nerve-cancer cell cross-talk during cancer progression. [25 d,46,54] Fluorescence imaging has tremendous clinical potential for image-guided surgery because it is typically much easier to be visually interpreted than MRI or US.…”
Section: Challenges and Future Opportunitiesmentioning
confidence: 99%
“…For example, an ROS-activatable probe can be utilized for in vivo visualization of an inflamed nerve. [53] Another factor to be considered for fluorescent tags is the hydrophobicity. It has previously been shown that hydrophobic fluorophores have higher affinity to the myelin sheath in both the PNS and CNS; however, this commonly resulted in nonspecific accumulations in adipose tissue and may affect the migration of targeted agents along nerve fibers.…”
Section: Development Of Nerve-specific Targeting Agentsmentioning
confidence: 99%